2008
DOI: 10.3181/0708-rm-212
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor 1 Is Expressed in Mouse Developing Testis and Regulates Somatic Cell Proliferation

Abstract: Testicular development occurs prenatally in mammals. The developmental underlying mechanism is only partially understood. The aim of the present investigation was to study the expression of the gene coding for insulin-like growth factor 1 (Igf-1) and Igf-1 type 1 receptor (Igf-1r) and their respective proteins in mouse Sertoli and Leydig cells at gestation day 12 (E12)-E18. Moreover, we sought to determine the effect of IGF-1 on the proliferation of both cell types and to establish the signal transduction mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 37 publications
1
19
0
1
Order By: Relevance
“…In mammals, Igf ligands can reach the testes from extratesticular sites via the circulation but can also be derived from different testicular cell types, such as Sertoli and Leydig cells in mice (61) or different germ cell types in stallion (62). Both somatic (Leydig and Sertoli cells) and germ cells (mainly spermatogonia and spermatocytes) have been identified as Igf1 sources also in fish (57,58,63,64).…”
Section: Discussionmentioning
confidence: 97%
“…In mammals, Igf ligands can reach the testes from extratesticular sites via the circulation but can also be derived from different testicular cell types, such as Sertoli and Leydig cells in mice (61) or different germ cell types in stallion (62). Both somatic (Leydig and Sertoli cells) and germ cells (mainly spermatogonia and spermatocytes) have been identified as Igf1 sources also in fish (57,58,63,64).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the systemic role of IGF-I, it also has important autocrine and paracrine roles at the cellular level, regulating mitosis, apoptosis, and cellular differentiation. The testes are clearly a site of IGF-I biosynthesis and action (Wang and Hardy, 2004); LH stimulates IGF-I secretion in rodent testes (Cailleau et al, 1990) and both IGF-I and its receptors have been detected in Leydig cells, Sertoli cells, and spermatocytes in various species (Hansson et al, 1989;Villalpando et al, 2008). Wang and Hardy (2004) evaluated a target gene deletion of IGF-I in the testes and concluded that both IGF-I and LH are critical factors in determining Leydig cell numbers and their steroidogenic capacity (Wang and Hardy, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Igf1 and Igf1r are expressed in Sertoli and Leydig cells from E12-E18 during mouse development, with highest levels of both proteins detected at E18 [52]. Increased expression of the IGF1R was detected in adult Irs2 -deficient testes (Fig.…”
Section: Discussionmentioning
confidence: 86%